Analisis Kepercayaan Dan Jangka Waktu Kredit Terhadap Penyaluran Kredit Pada Bank Sulselbar Makassar - Rahmi Rahmi; Mohamad Ali Wairooy Ali Wairooy (Fakultas Ekonomi Universitas Indonesia Timur, 2021)
This study aims to test and analyze the Analysis of Trust and Credit Period for Credit Distribution at the Sulselbar Makassar Bank. Collecting data using primary data obtained from questionnaires using purposive sampling techniques and determining the amount using unknown population, 96 respondents were obtained. The results of the questionnaire have been tested for validity and reliability, also tested the classic assumption in the form of the Normality assumption and the Heteroscedasticity assumption. The data analysis method uses multiple regression techniques. Based on partial analysis (t-test) and simultaneously (Test-f) it turns out the results of the study prove that all hypotheses are accepted because Trust and Credit Periods are partially and simultaneously have a positive and significant effect on Credit Distribution at Bank Sulselbar Makassar. Keywords: Trust, Credit Period, Credit Distribution